The Cultural Trade Index : An Introduction - Kabanda, Patrick (World Bank Policy Research Working Paper, 2016)
The Cultural Trade Index aims to shed light on cultural trade and stimulate interest in how this little-known area can contribute to economic diversification, boost shared prosperity, and reduce extreme poverty. As the first index of its kind, the Cultural Trade Index would gather cultural trade data scattered across different sources, place them in one place, and show how countries are performing. The key objective is to help inform decision making to advance cultural trade for development. Since culture is not restricted to monetary gain, a Cultural Exchange Index could also be created to complement the Cultural Trade Index. The Cultural Exchange Index would rank countries according to their participation in international cultural exchanges. Comprehensive research efforts would be needed for these ideas to make meaningful contributions to cultural trade and development policy.
Keywords: Culture in Development, Creative Economy, Cultural Policy, Cultural Statistics, Cultural Trade